Notes on Megalotomus Fieber, 1860 in the Palaearctic Region (Hemiptera, Heteroptera, Alydidae) - Yi, Wenbo; Wang, Shijun; Zhang, Hufang; Bu, Wenjun (Zootaxa, 2022)
The Palaearctic species of the genus Megalotomus Fieber, 1860 are reviewed. The diagnoses and distributions of Megalotomus species are updated. Megalotomus angulus (Hsiao, 1965) comb. nov. is transferred from Alydus Fabricius, 1803 and re-described based on type material from China. Megalotomus obtusus Ghauri, 1972 syn. nov. is proposed as a new junior synonym of M. angulus (Hsiao, 1965) comb. nov. based on examination of type material from Pakistan. Photographs of adults and illustrations of male external genitalia are provided. A review of their distribution and a key for their identification are provided.